Influence of tannins supplementation on growth performance, dietary net energy and carcass characteristics of yearling steers fed finishing diet containing dried distillers grains with solubles - RIVERA-MÉNDEZ, CARLOS R; PLASCENCIA, ALEJANDRO; TORRENTERA, NOEMÍ; ZINN, RICHARD A (The Indian Journal of Animal Sciences, 2016)
Finishing diets containing 15% DDGS with 0, 0.22, and 0.44% condensed tannin did not affect average daily gain, but linearly increased dry matter intake. Tannin supplementation linearly decreased gain efficiency, and estimated dietary NE. Carcass characteristics were not affected by tannin supplementation. Therefore, tannins supplementation did not enhance growth performance of yearling steers fed a high-energy finishing diet containing 15% DDGS, and may decrease efficiency of energy utilization.